Pengaruh disiplin belajar terhadap karakter tanggung jawab siswa kelas VIII SMP Negri 9 Tebo: Pengaruh disiplin belajar terhadap karakter tanggung jawab siswa - Usmanto, Heri; Setya Ningsih, Ayu (Citizenship Education, Faculty of Education, Jambi University, 2023)
Setyaningsih. Come on. 2021. â€œThe Influence of Learning Discipline on the Responsible Character of Class VIII SMP Negeri 9 Teboâ€. Thesis. Pancasila and civic education. Department of Social Science Education FKIP Jambi University. Keywords: Learning Discipline, responsibility character The results of preliminary observations and information obtained from teachers at SMP Negeri 9 Tebo indicate that there are forms of behavior that lead to the development of poor character of responsibility. These forms of behavior include not obeying school rules, lack of manners, gathering in a place to play online games via cellphone, lazy to do assignments and lack of focus. to the lesson so that it can interfere with their responsibilities as a student. These behaviors of course have a relationship with the assistance of children by adults and the discipline of children. The purpose of the study was to determine the effect of learning discipline on the responsibility character of eighth grade students of SMP Negeri 9 Tebo. The type of research used in this research is expost facto research. The population of this study was 89 students. The sample in the study only amounted to 20 students. The independent variable in this research is learning discipline. The dependent variable in this study is the character of responsibility. Based on the results and data processing of learning disciplines with a sample of 20 people, the total score was 2116 with an average value of 105.8, and a standard deviation of 4.79, the highest score was 112 and the lowest was 94. For responsibility character data with a sample of 20 people, the total score is 1552, with an average value. For the normality test Lo < Ltable, the data from the two variables have a normal data distribution because, for the learning discipline data Lo (0,1056) < Ltable (0,190), and the character of responsibility data (0,1736) < Ltable (0,190) . homogeneity of variance test is the F test. With n = 20, S12 = 22.91 and S22 = 15.20 obtained Fcount = 1.506 Next with dk numerator (V) = 20 obtained Ftable = 3.49. By using the formula (n-2) 20â€“2 = 18 at = 0.05, then with dk 18, for the two-sided test t 0.95 = 1.7341 it is easy to see that t_(count=) 2.273 > t_table 1, 7341 then there is the effect of learning discipline on the responsibility character of class VIII students of SMP Negeri 9 Tebo. The conclusion of the research is that there is an effect of learning discipline on the responsibility character of class VIII students of SMP Negeri 9 Tebo.